2020
DOI: 10.1002/ptr.6723
|View full text |Cite
|
Sign up to set email alerts
|

The effects of garlic (Allium sativum) supplementation on inflammatory biomarkers, fatigue, and clinical symptoms in patients with active rheumatoid arthritis: A randomized, double‐blind, placebo‐controlled trial

Abstract: Based on the antiinflammatory properties of garlic, current study was conducted to evaluate the garlic supplement effects on serum levels of some inflammatory biomarkers, clinical symptoms, and fatigue in women with active rheumatoid arthritis. In this randomized, double-blind, placebo-controlled trial study, 70 women with RA were randomly divided into two groups: The intervention group was supplemented with 1,000 mg of garlic, and the control group received placebo for 8 weeks. At baseline and at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 46 publications
2
28
1
Order By: Relevance
“…One double-blind randomized controlled trial by Moosavian et al with a low risk of bias assessed the effect of a garlic supplementation (1000 mg garlic powder tablets equivalent to 2.5 g of fresh garlic, i.e., half of a garlic clove) on RA activity in 70 patients (35 per group) [ 11 , 12 ]. There was no significant difference between the two groups for DMARDS and corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One double-blind randomized controlled trial by Moosavian et al with a low risk of bias assessed the effect of a garlic supplementation (1000 mg garlic powder tablets equivalent to 2.5 g of fresh garlic, i.e., half of a garlic clove) on RA activity in 70 patients (35 per group) [ 11 , 12 ]. There was no significant difference between the two groups for DMARDS and corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
“…Tolerance was good in the six studies: stomach pain in one patient with garlic and saffron supplementation [ 11 , 12 , 18 ] and mild fever and throat infection in one patient with curcumin supplementation [ 13 ]. Clinical trials assessing saffron, curcumin, and garlic supplementation showed similar mild adverse events between control and experimental groups [ 20 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmful agents activate inflammatory cells, such as neutrophils and macrophages, and induce the release of proinflammatory molecules, including C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6). Although inflammation is an essential component for a proper immune response and the maintenance of homeostasis in the body [ 2 , 3 ], chronic inflammation plays a key role in the onset and progression of several chronic diseases, including diabetes [ 4 ], cardiovascular diseases [ 5 ], neurodegenerative diseases [ 6 ], rheumatoid arthritis [ 7 ], and cancer [ 8 ]. Popular approaches suggest controlling inflammation through pharmacological [ 9 , 10 , 11 ] and dietary interventions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, organosulfur compounds in garlic ( Allium sativum L ) such as allicin and s‐allylcysteine are thought to be the main bioactive compounds responsible for the management of blood pressure, inflammation, and hepatic steatosis (Soleimani et al, 2020). These compounds improve blood pressure and inflammation by inhibiting the angiotensin‐converting enzyme, and transcription factor NF‐κB (Moosavian et al., 2020; Xiong et al., 2015b). At present, based on our knowledge, no clinical evidence exists regarding the effect of garlic consumption on blood pressure, and hs‐CRP level among patients with NAFLD.…”
Section: Introductionmentioning
confidence: 99%